Efektifitas Penerapan Project Based Teaching Module dalam Mengangkat Tingkat Kreativitas Belajar Siswa - Ratnaya, I Gede; Dewi, Putu Yulia Angga; Diarini, I Gusti Ayu Agung Sinta; Mujahidin, Syamsul (STAHN Mpu Kuturan Singaraja, 2023)
The aim of this research is to see the level of effectiveness of implementing the project based teaching module on the topic of Culinary Basics. The uniqueness of this research lies in the responses of students who use the module. The module content is very interesting and varied so that it can increase student interest and stimulate creativity. Students become interested in reading because usually students only use books that are still rigid. The examples given in the module are very up to date. The method used in this research is a quasi experimental design research method with a control group and a random research sample. Data analysis techniques were carried out qualitatively (input criticism, suggestions) and quantitative (respondent assessments in the form of numbers on the questionnaire and observation sheet provided). The data collection technique used Pretest - Posttest Control Group Design which was analyzed using analysis prerequisite tests through normality tests and inferential statistics through t-tests (independent sample T-tests) to see differences in the average group learning outcomes. The population of this class is 40 people. The samples used were 30 with random sampling. Testing the effectiveness of using project based teaching module products in increasing the creativity of Dwi Tunggal Tourism Vocational School students was carried out using a two-tailed t-test. The tcount = 2.133 while the ttable value = 2.000, this shows that tcount is greater than ttable with a significance level of 0.05. So, the creativity of Dwi Tunggal Tourism Vocational School students who take part in learning using project based teaching modules is higher than the creativity of Dwi Tunggal Tourism Vocational School students who take conventional learning.